Numeration Literacy in Integral Calculus Problem Solving reviewed from Student Learning Style - Nurina Kurniasari Rahmawati; St Budi Waluya; Isti Hidayah; Rochmad Rochmad (International Conference on Science, Education, and Technology, 2021)
This research aims to find out how numerical literacy in solving calculus II problems as seen from the student's learning style. The subjects in this research were learners of STKIP Kusuma Negara Jakarta who had attended calculus II courses in the 2020/2021 school year, namely 2 students each with Visual, auditorial, and types of kinesthetic learning with purposive sampling techniques. The instruments in this study are researchers, a test to measure numerical literacy in the form of essay questions consisting of 4 questions, interview guidelines, and questionnaires to find out the student's learning style consisting of 60 points of statement. The results showed that out of 28 students who were polled there were 9 it was not possible to assess the learning style of students with visual learning styles, 14 students with auditory learning styles, 3 students with kinesthetic learning styles, and 2 students. Students who have forms of auditorial learning tend to have had higher numerical literacy than students who have visual and kinesthetic types of learning, and students whose type of visual learning tends to better for better numerical literacy than students Which have forms of kinesthetic learning. Students who have an auditory learning style have high numerical literacy, students who have a visual style of learning have moderate numerical literacy, and students with kinesthetic learning style have low numerical literacy.